The emergence of imagination and altruism in human evolution: key elements in a new-style natural theology - Barrett, Peter (Journal of Theology for Southern Africa, 2015)
A new-style natural theology is introduced which aims at a grand narrative of divine creation, based on the scientific accounts of cosmic, biological and human evolution. It features the emergence of imagination as a high point in the evolutionary development of humankind, creating the possibility of abstract thought, making for moral and aesthetic awareness and creativity, and playing a key role in the phenomenon ofhuman altruism. After presenting a detailed account of the nature and background story of this singular cognitive attribute, we discuss a recently presented ‘new natural theology’ concerning altruism at its morally highest levels. We then describe elements of a Trinitarian-based grand narrative which embraces such altruism - one which stands in sharp contrast to the natirral theologies oftwo South African theologians, briefly outlined here for comparison. Such a narrative seems a particularly appropriate basis for the church’s engagement in the big issues of today’s world..
Keywords: Altruism; Coakley; Sarah; 1951-‏; Conradie; Ernst M; Creation – History of doctrines – 1900; Du Toit; Cornel W; Evolution; Imagination; Natural theology; Nature – Religious aspects – Christianity; Peer reviewed; Theological anthropology – Christianity